EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA BALOK CUISENAIRE TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II UPT SPF SD INPRES BONTOMANAI - Sri Susanti; Andi Husniati; Kristiwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The main problem in this research is whether the cooperative learning model assisted by Cuisenaire block media is effective on class II mathematics learning outcomes at UPT SPF SD Inpres Bontomanai. This research aims to determine the effectiveness of the cooperative learning model assisted by Cuisenaire block media on class II mathematics learning outcomes at UPT SPF SD Inpres Bontomanai. This type of research is pre-experimental. The research design is a Pretest-Posttest Design, namely an experiment whose implementation only involves one class as the experimental class without any comparison class (control class). The population in this study were all class II UPT SPF SD Inpres Bontomanai students, totaling 63 students and the sample was class II A II UPT SPF SD Inpres Bontomanai students, totaling 33 students. The research instruments used were learning outcomes tests, observation sheets, questionnaires and student responses. The data analysis techniques used are descriptive statistical analysis techniques, data analysis on improving learning outcomes, and inferential statistical analysis. The research results show that the average mathematics learning outcome before the cooperative learning model assisted by cuisenaire block media was implemented was 72.88 and after the cooperative learning model assisted by cuisenaire block media was implemented was 81.97. The results of the activity analysis of class II UPT SPF SD Inpres Bontomanai were 83.8% in the active category, and the results of the analysis of student responses were 83.15% of students with positive responses and 12.42% of students with negative responses. Based on the results of the SPSS version 27 analysis, it appears that the sig value = 0.000 < 0.05 indicates that the average student learning ability test results after learning mathematics using cuisenaire block media is 0.05 > µ ≥ 81.97, this means that Hₒ rejected and H₁ accepted with an average student posttest score of 81.97, which means an increase in mathematics learning outcomes for class II UPT SPF SD Inpres Bontomanai students. Based on the results of the research above, it can be concluded that the learning outcomes of class II students at UPT SPF SD Inpres Bontomanai using Cuisenaire block media are classified as effective.